The Impact of TBI on Intermediate Students' Writing skills in Online Classes at a Private Institute in Cartagena de Indias - Adriana Garcia-Echeverry; Alexandra Novozhenina (Asociación Colombiana de Profesores de Ingles, 2023)
This qualitative research project aims to determine the impact that Task-Based Instruction had on fifteen Intermediate English language students´ writing skills in online classes at a private institute in Cartagena. A journal, a questionnaire, and a checklist were used as instruments to collect information during the diagnostic stage. During the action stage, six workshops were implemented, each with a different writing strategy: webbing, peer-editing, asking questions to revise writing, revising and editing, using templates, and reorganizing ideas. At this stage, the same instruments were used to measure the impact of the strategy and to achieve the research objectives. Results show that implementing six online workshops predicated on the task-based instruction helped the students to improve their writing, learning new vocabulary, use ICT tools, and writing strategies, thus having a positive impact on their English language learning process not only in writing but also in other skills. TBI was favorably accepted by learners and affected positively their writing skills.